The Outcomes of Sodium-Glucose Co-transporter 2 Inhibitors (SGLT2I) on Diabetes-Associated Neuropathy: A Systematic Review and meta-Analysis - Kandeel, Mahmoud (Frontiers in Pharmacology, 2022)
Diabetes mellitus (DM) is one of the leading causes of morbidity and mortality worldwide. DM patients with diabetic neuropathy (DN) usually present with distal pain, sensorimotor polyneuropathy, postural hypotension, or erectile dysfunction. They also may present with other nerve pathologies such as inflammatory neuropathies and carpal tunnel syndrome. We conducted a systematic review and meta-analysis to assess the benefits of using sodium–glucose co-transporter-2 inhibitors (SGLT2Is) to manage DN. An extensive systematic literature review was conducted to include all articles published up to 24 February 2022. All clinical studies included patients with DM and reported the outcomes of SGLT2I on diabetes-associated neuropathy. Six studies were identified for meta-analysis, including a total of 5312 diabetic patients. The average age of the included patients ranged from 41 to 74 years and 34 to 73 years in the SGLT2I treatment and control groups, respectively. SGLT2I moderately improved the manifestations of diabetic peripheral neuropathy events and nerve conduction velocity. Furthermore, the SGLT2I treatment group had a statistically significant higher mean heart-to-mediastinum ratio (MD 0.41; 95% 0.17, 0.64; p = 0.0006). However, the mean heart rates (MD -4.51; 95% -10.05, 1.04; P=0.11) and wash out rates (MD 2.13; 95% -8.48, 12.75; p = 0.69) were not significantly different between the two groups. SGLT2Is could therefore be considered neuroprotective in patients with DN, possibly by considerably increasing the sensory and motor nerve conduction velocity, improving the clinical manifestations of DPN, and reducing sympathetic nervous system activity.